A CRISPR/Cas9 Toolbox for Multiplexed Plant Genome Editing and Transcriptional Regulation . Issue 2 (21st August 2015) - Lowder, Levi G.; Zhang, Dengwei; Baltes, Nicholas J.; Paul, Joseph W.; Tang, Xu; Zheng, Xuelian; Voytas, Daniel F.; Hsieh, Tzung-Fu; Zhang, Yong; Qi, Yiping
Abstract : A CRISPR/Cas9 toolbox enables multiplex genome editing and transcriptional regulation of genes in plants. Abstract: The relative ease, speed, and biological scope of clustered regularly interspaced short palindromic repeats (CRISPR )/CRISPR-associated Protein9 (Cas9)-based reagents for genomic manipulations are revolutionizing virtually all areas of molecular biosciences, including functional genomics, genetics, applied biomedical research, and agricultural biotechnology. In plant systems, however, a number of hurdles currently exist that limit this technology from reaching its full potential. For example, significant plant molecular biology expertise and effort is still required to generate functional expression constructs that allow simultaneous editing, and especially transcriptional regulation, of multiple different genomic loci or multiplexing, which is a significant advantage of CRISPR /Cas9 versus other genome-editing systems. To streamline and facilitate rapid and wide-scale use of CRISPR /Cas9-based technologies for plant research, we developed and implemented a comprehensive molecular toolbox for multifaceted CRISPR /Cas9 applications in plants. This toolbox provides researchers with a protocol and reagents to quickly and efficiently assemble functional CRISPR /Cas9 transfer DNA constructs for monocots and dicots using Golden Gate and Gateway cloning methods. It comes with a full suite of capabilities, including multiplexed gene editing and transcriptional activation or repression of plant endogenous genes. We report the functionality and effectiveness of this toolbox in model plants such as tobacco ( Nicotiana benthamiana ), Arabidopsis ( Arabidopsis thaliana ), and rice ( Oryza sativa ), demonstrating its utility for basic and applied plant research.